Caring for the future : report of the Independent Commission on Population and Quality of Life - Harrison, Paul.; Independent Commission on Population and Quality of Life. (Oxford : Oxford University Press, 1996)
This timely, path-breaking report examines the challenges that face all countries, both rich and poor, in the last years of the century. The Independent Commission on Population and Quality of Life, headed by Maria de Lourdes Pintasilgo, former Prime Minister of Portugal, outlines a radical agenda to confront the economic, human, and environmental crises facing the world today.
Throughout the book are powerful personal testimonies from regional hearings of the commission in Africa, Asia, Latin America, USA, Canada, and eastern Europe.
Introduction: A World in Transition -- 1. The Population Challenge -- 2. The Social Challenge: Facing Poverty -- 3. The Ecological Challenge -- 4. The Economic Challenge: A New Production and Consumption Model for the Globalized Economy -- 5. Focusing on the Goal: Sustainable Improvement of the Quality of Life -- 6. Respecting the Limits: The Carrying Capacity of the Earth -- 7. Responding to Needs: The Caring Capacity of Humankind -- 8. Attitudes towards Population Change: A Paradigm Shift -- 9. Redefining Work -- 10. Towards an Alternative Edticational Policy -- 11. From Medical to Health Care -- 12. Reproductive Choices -- 13. Empowering Women -- 14. Mobilizing Social Forces: Towards a New Social Contract -- 15. Mobilizing Resources: Tapping the Markets -- 16. Conclusions and Recommendations.
Includes index.
Keywords: Quality of life; Sustainable development; Population policy; Women in development